PREVALENCE OF HYPERTENSION IN WORKERS OF VEGETABLE OIL REFINERIES IN TEHRAN - Dariush Parvizpour (Tehran University of Medical Sciences, 1978)
968 male workers employed in five vegetable oil refineries were studied to discover the effects of age, length of employment and smoking habit on the prevalence of hypertension. The results obtained indicate that the overall prevalence of hypertension is 6.61% showing a direct relationship to the age. Considering the length of employment only, in the workers aged 50 and above, there is also a direct relation between the length of employment and prevalence of hypertension. Furthermore, the results show that not only smoking causes elevation of blood pressure, but the number of cigarettes smoked per day is also important, i.e. the workers who smoke more have a higher prevalence of abnormal pressure.